Problem Based Learning untuk Meningkatan Kreativitas Mahasiswa Berbasis Literasi Digital - Ika Trisni Simangunsong; Deo Demonta Panggabean; Dede Parsaoran Damanik (Departement of Mathematics Education, 2023)
Problem based learning is a model of learning that can be increased student creativity. This research is a classroom action research (CAR). Based on the results of research, it as found that 44% were in the reached category, while in cycle 2 there were 66% of students in the reached category. It was showed an increase the creativity of student in digital literacy through the application of PBL UDA FKIP’s student